Frequency of pelvic asymmetry among medical students of Karachi - Yaseen, Amna; Subhan, Sana; Hameed, Taiba; Akhter, Saeed (International Journal of Endorsing Health Science Research, 2018)
Background: Assessment of the pelvis is a complex integration with spine and lower extremities and is prone to multiple dysfunctions. Physiotherapists in routine rarely assess pelvis associated musculoskeletal abnormalities. This study was aimed at finding the frequency of pelvic-asymmetry in medical students of Karachi. Methodology: An observational cross-sectional study was conducted from 28th November 2017 to 6th February 2018 to measure asymmetry of the pelvis manually. A sample of 154 medical students was calculated through Open Source Epidemiologic Statistics for Public Health (Open Epi) version 3.0 with a confidence level of 95%. Non-probability purposive sampling technique was used. An informed consent was taken and data was collected from participants aged between 18-25 years through a self-generated questionnaire. Participants with Congenital abnormalities or fracture of lower limb or complain of nerve root pain, any spinal pathology/tumor/surgery of lower limb were excluded from the study sample. Data was analyzed using Statistical Project of Social Science (SPSS) version 20. Results: According to the results 43.5% of the study subjects were observed having pelvic asymmetry. Furthermore, 41.0% participants were spending <3 hours in a constant standing position were observed with the asymmetrical pelvis, while 40.5% participants with pelvic asymmetry work for >3 hours standing constantly. Only 41.5% of participants with low back pain were observed having an asymmetrical pelvis. Conclusion: It can be concluded from the study results that there is a high prevalence of pelvic asymmetry observed among medical students of Karachi. Moreover, knee and ankle joint pain due to constant standing is highly associated with asymmetrical pelvis as compared to hip pain.